1966
DOI: 10.1073/pnas.56.2.440
|View full text |Cite
|
Sign up to set email alerts
|

Replication of semliki forest virus: three forms of viral RNA produced during infection.

Abstract: The mechanism for the replication of animal RNA viruses has been the subject of intense investigation. With few exceptions (Gomatos and Tamm, 1963; Sonnabend et al., 1964), however, these studies have been on picornaviruses, specifically poliovirus (Baltimore, Becker, and Darnell, 1964) or members of the encephalomyo-(arditis group (Montagnier and Saunders, 1963). This report will present studies on the replication pattern of Semliki Forest virus, a group A arbovirus. Semliki Forest virus has some properties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
0

Year Published

1968
1968
1979
1979

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 11 publications
5
85
0
Order By: Relevance
“…It has been demonstrated that arbovirus RNA synthesis in infected chick embryo fibroblasts resembles in principle that of picornaviruses (Sonnabend et aL I964;Friedman, Levy & Carter, 1966 ). The present study deals with the intracytoplasmio localization in infected chick embryo fibroblasts of Sindbis virus RNA, and with the time course of synthesis of the different viral RNA species, coat proteins and virions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that arbovirus RNA synthesis in infected chick embryo fibroblasts resembles in principle that of picornaviruses (Sonnabend et aL I964;Friedman, Levy & Carter, 1966 ). The present study deals with the intracytoplasmio localization in infected chick embryo fibroblasts of Sindbis virus RNA, and with the time course of synthesis of the different viral RNA species, coat proteins and virions.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse experiments with [~H]-uridine demonstrated that in Semliki Forest-infected cells a partially RNase-resistant 2o S RNA appears first and was followed by RNA of ~6 S and 42 S (Friedman, Levy & Carter, 1966;Cartwright & Burke, 197o). Thus it was possible that these components were in precursor-product relationship.…”
Section: Precursor-product Relationships Of Semliki Forest Virus Rna'smentioning
confidence: 99%
“…In this paper we use several different procedures to examine the virus-specific RNA from cells infected with Semliki Forest virus, an alphavirus, for the presence of poly A tracts. Such viruses are of interest because the virus particle contains a molecule of single-stranded RNA which is infectious (Friedman, Levy & Carter, 1966) and which therefore is presumed to act as a messenger for its own RNA replicase. In addition, the infected cell contains three other single-stranded RNAs of the same polarity, two of which have been shown to be associated with polysomes (Kennedy, i97z;Moshowitz, I973;Rosemond & Sreevalsan, 1973) and are therefore putative messengers.…”
Section: Introductionmentioning
confidence: 99%